An early locus of associative and categorical context effects in speech production: evidence from an ERP study using the picture–word interference paradigm. Issue 10 (26th November 2017) - Wong, Andus Wing-Kuen; Chiu, Ho-Ching; Wang, Jie; Cao, Jinlu; Wong, Siu-San; Chen, Hsuan-Chih
ABSTRACT: A picture–word interference (PWI) experiment with concurrent electroencephalogram (EEG) recording was conducted to investigate the time course of categorical and associative context effects in spoken word production. Mandarin-speaking participants were asked to name individually presented target pictures and ignore a superimposed two-character Chinese word distractor. The target and distractor were either categorically related (belonging to the same semantic category), associatively related (semantically related but not categorically related), phonologically related, or unrelated. The typical categorical interference (slower picture naming with a categorically related distractor relative to an unrelated control) was found. Furthermore, significant event-related brain potential effects were obtained in categorical and associative conditions in the time window between 275 and 450 ms post-target. By using response-locked analysis, significant effects of Target-distractor Relatedness were observed only in the associative condition within the 300-ms pre-response period. These results are consistent with the theories that assume lexical selection by competition in explaining the categorical interference effect.